Laboratory studies of the effects of selected tropical fruits on the larvae of Dacus dorsalis, Hendel - Ibrahim, Abdul Ghani; Abdul Rahman, Mohd Dzur (1982)
A laboratory study (27° C-30° C) on the suitability of tropical fruits for the larval development shows that it is in the order of : Papaya> carambola > banana> mango = water-melon> jackfruit > citrus> pineapple. In a suitable host i.e. papaya, the weight of the pupa was 11.6 g and life-cycle was 20.4 days. In the least suitable host i.e. pineapple, the weight of pupa was 4.9 g and life-cycle was 17.4 days. With papaya as food, the life-cycle of D. dorsalis depended on the density of the larvae within the food. A density of 10 larvae in 20 g of food had a life-cycle of21.7 days, whereas a density of50 larvae in the same quantity of food had a life-cycle of 15.1 days. The percentage of adult emergence decreased with increase in the larval density.